2009
DOI: 10.3382/japr.2007-00094
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and production costs of composting breeder and pullet litter with eggshell waste

Abstract: Phosphorus runoff from the land application of poultry litter has become a concern in watersheds in the Ozark Plateau region, prompting local growers to use alternative litter management practices. One option is the export of excess poultry litter from producers in nutrient-surplus watersheds to users located in areas where nutrient loads are not problematic. In 2006, nearly 100,000 tons of broiler and turkey litter was exported by BMPs Inc., a nonprofit corporation providing litter management services. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…However, eggshells are a good calcium resource as a nutritional supplement, which enjoy great business prospects [1,2]. The eggshell calcium carbonate had been traditionally utilized as a fertilizer, soil conditioner or an additive for animal feed due to its high nutrient content [3][4][5][6][7][8]. Naves also found that traditional meals fortified with eggshell powder could significantly contribute to the adequate calcium intake and to prevent calcium deficiency, such as osteoporosis, in individuals of different age groups and socioeconomic statuses social levels [1].…”
Section: Introductionmentioning
confidence: 98%
“…However, eggshells are a good calcium resource as a nutritional supplement, which enjoy great business prospects [1,2]. The eggshell calcium carbonate had been traditionally utilized as a fertilizer, soil conditioner or an additive for animal feed due to its high nutrient content [3][4][5][6][7][8]. Naves also found that traditional meals fortified with eggshell powder could significantly contribute to the adequate calcium intake and to prevent calcium deficiency, such as osteoporosis, in individuals of different age groups and socioeconomic statuses social levels [1].…”
Section: Introductionmentioning
confidence: 98%
“…Thus, even if the starting mixture contains about 30 % of ES, no negative influence is observed in GI parameter. Lower GI (from 32.5 to 50 %) were obtained by [13] in composts produced with eggshell waste and breeder and pullet litter, which points out that the phytotoxic characteristics of the composts produced with eggshell waste could only be attributed to the properties of the animal manure used in the windrows composition.…”
Section: Phytotoxiticity and Stabilitymentioning
confidence: 92%
“…To the best of our knowledge, eggshell waste composting with other ABP has not been considered. The only study found in the literature has used microbial inoculants to aid in the humus buildup [13].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, due to the high nutritional contents of ES, namely calcium, its application to acid soils with calcium deficiency may constitute an option to promote ES transformation into a value-added product and consequently recover a natural resource contained in this by-product. Nonetheless, according to our l<nowledge, industrial ES composting is scarcely addressed in literature (Kemper & Goodwin 2009). …”
Section: Introductionmentioning
confidence: 98%